Manuel de Mier y Terán y la insurgencia en Tehuacán - Sordo Cedeño, Reynaldo (El Colegio de México, A.C., 2009)
This paper seeks to explain Manuel de Mier y Terán's  role in the Independence struggle, particularly as head of the patriotic forces of the partido of Tehuacán, Puebla, between August 16, 1815 and January 21, 1817. The essay articulates three processes of the independence  struggle in this region: Mier y Terán's military career before 1815, the spatial characteristics at Tehuacán and its surrounding areas and, finally, Mier y Terán's  political and military strategy to invigorate insurgency in adverse conditions.